Gene-Environment Interaction Research and Transgenic Mouse Models of Alzheimer's Disease. (28th December 2010) - Chouliaras, L.; Sierksma, A. S. R.; Kenis, G.; Prickaerts, J.; Lemmens, M. A. M.; Brasnjevic, I.; van Donkelaar, E. L.; Martinez-Martinez, P.; Losen, M.; De Baets, M. H.; Kholod, N.; van Leeuwen, F. W.; et al.
Abstract :